Enhanced anaerobic digestion of corn stover by thermo-chemical pretreatment - Fang, Wang; Weisheng, Niu; Andong, Zhang; Weiming, Yi (International Journal of Agricultural and Biological Engineering, 2015)
In order to solve the problem of lignocellulose degraded speedily and efficiently in anaerobic digestion, the thermo-chemical pretreatment was applied to enhance biogas production from corn stover. Corn stover was thermo-chemical pretreated with a fluidized bed pyrolysis reactor at 180℃, 200℃ and 220℃, respectively. Lignin degradations during pretreatment were 15.07%, 32.57% and 33.31%, respectively. The Scanning Electron Microscope (SEM)images and Fourier Transform Infrared Spectroscopy (FTIR) spectra confirm that the thermo-chemical pretreatment can change the structure of corn stover and make lignin content decrease. The thermo-chemical pretreated corn stover was digested using a 2-L fermentation reactor. Experimental results showed thermo-chemical pretreatment could improve biodegradability and enhance biogas production. The highest total biogas production was 23 319 mL for 20 d which was 10.0% higher than that of the untreated corn stover.DOI: 10.3965/j.ijabe.20150801.011Citation: Wang F, Niu W S, Zhang A D, Yi W M. Enhanced anaerobic digestion of corn stover by thermo-chemical pretreatment. Int J Agric & Biol Eng, 2015; 8(1): 84－90.